Complete Genome Sequence of Microcystis aeruginosa NIES-2549, a Bloom-Forming Cyanobacterium from Lake Kasumigaura, Japan - Yamaguchi, Haruyo (Genome Announc, 2015)
Microcystis aeruginosa NIES-2549 is a freshwater bloom-forming cyanobacterium isolated from Lake Kasumigaura, Japan. We report the complete 4.29-Mbp genome sequence of NIES-2549 and its annotation and discuss the genetic diversity of M. aeruginosa strains. This is the third genome sequence of M. aeruginosa isolated from Lake Kasumigaura.